Thursday

October 23, 2014

October 23, 2014

Posted by **Megan Watt** on Thursday, March 17, 2011 at 10:06pm.

a)f(-3)

b) f(-x)

c)-f(x)

d)f(x-3)

e)f(x+a)

- algebra -
**Cassie**, Thursday, March 17, 2011 at 11:44pmf(-3) = -3(-3)+5

= 9+5

= 14

now do the same for the rest..

f(x-3)= -3(x-3)+5

= -3x+9+5

= -3x+14

**Answer this Question**

**Related Questions**

Algebra - Which of the following is not a step in graphing a quadratic function...

Algebra - Complete the table for each function. 1. f(x) = √x The x values ...

Calculus, check my answers, please! - Could someone tell me if I'm right, and ...

Algebra 1 (Reiny or Kuai) - Give the domain and range values of each relation. ...

Algebra 2 - I need to find x of the quadratic function y=-5/3x^2-x-4. I'm ...

Calculus - Find all numbers c that satisfy the conclusion of Rolle's Theorem for...

College alg - Analyze the graph of the following function as follows: (a) Find ...

Algebra - That is not what the ? is asking. The ? is asking about how to get the...

Algebra - Evaluate the following function at the indicated values. H(x) = 2x (a...

algebra - Let the set of ordered pairs (x, y)= {(1, 2), (2, 4), (1, 3), (3, 4)} ...